Phytochemistry of Punica granatum Fruit: Its Nutritional and Biological Potential - Saba Kiran; Asma Aslam; Asma Parveen; Muhammad Dilshad; Shabbir Hussain (Bioactivities, 2024)
The present review provides a comprehensive overview of the phytochemistry, nutritional composition, and therapeutic implications associated with the consumption of pomegranate (Punica granatum) fruit, renowned for its dual role as a taste delicacy and a medicinal agent. A detailed exploration of the phytochemical composition is undertaken. Recognized for its myriad health benefits, this fruit has been historically employed as a remedy for diverse disorders, with its leaves, peel, and bark demonstrating efficacy in treating gastrointestinal issues leading to diarrhea. Notably, pomegranate juice has been utilized in treating cholera, while the oil extracted from seeds exhibits notable efficacy in addressing skin and breast cancer. The review underscores the presence of bioactive compounds, including flavonoids, tannins, ellagitannins, catechin, and phenols, across various species of P. granatum. In addition to its rich phytochemical profile, pomegranate emerges as a nutritionally rich fruit, boasting significant quantities of vitamins C and D, magnesium, potassium, and dietary fibers. Its nutritional composition aligns with its therapeutic properties, encompassing anti-inflammatory, antioxidant, anticancer, and antimicrobial attributes. Notably, a single cup of pomegranate arils contains 72 calories, 16 g of carbohydrates, and 3 g of dietary fiber. This review serves to deepen our understanding of the multifaceted nature of pomegranate, and addresses emerging and technological advancements in pomegranate phytochemistry.